Problems Experienced By Inland Water Fishermen During The Pandemic (Covid-19): The case of Yozgat Province - Dartay, Mürşide (Umut SARAY, 2023)
The fishermen of Yozgat province, which is located in the middle of the steppe without a seashore, export the fish they catch abroad. During the pandemic, export in fisheries is restricted. For this reason, the aim of this study was to investigate the difficulties and problems experienced by fishermen in Süreyyabey and Gelin Güllü Dam lakes during the pandemic period covering the years 2020-2021 (March-2020; March 2021). In the study, 2 different questionnaire forms were carried out by face-to-face interviews with fishermen and cooperative presidents. As a result of the study; In the fishing period of July-December 2020 (6 months), there was no fish export and the fishery paused. In January-March 2021, exports started to be made at a certain quota. It was determined that 63.63% (n=21) of a total of 33 fishermen in Cekerek Dam Lake quit fishing, 66.66% (n=14) started farming, 33.33% (n=7) migrated, and 36.36% (n=12) continued fishing during the pandemic. In Gelin Güllü Dam lake, 35 % (n=7) of the total 20 fishermen quit fishing, 20 % (n=4) started farming and 65 % (n=16) continued fishing. Carp (Cyprinus carpio), Silver (Atherina boyeri), Siraz (Capoeta pestai), Sudak (Sander lucioperca) species were caught in the region during the pandemic The problems experienced by the fishermen in the region; unregulated fishing, marketing, it was determined that they did not receive any government support.

The fishermen of Yozgat province, which is located in the middle of the steppe without a seashore, export the fish they catch abroad. During the pandemic, export in fisheries is restricted. For this reason, the aim of this study was to investigate the difficulties and problems experienced by fishermen in Süreyyabey and Gelin Güllü Dam lakes during the pandemic period covering the years 2020-2021 (March-2020; March 2021). In the study, 2 different questionnaire forms were carried out by face-to-face interviews with fishermen and cooperative presidents. As a result of the study; In the fishing period of July-December 2020 (6 months), there was no fish export and the fishery paused. In January-March 2021, exports started to be made at a certain quota. It was determined that 63.63% (n=21) of a total of 33 fishermen in Cekerek Dam Lake quit fishing, 66.66% (n=14) started farming, 33.33% (n=7) migrated, and 36.36% (n=12) continued fishing during the pandemic. In Gelin Güllü Dam lake, 35 % (n=7) of the total 20 fishermen quit fishing, 20 % (n=4) started farming and 65 % (n=16) continued fishing. Carp (Cyprinus carpio), Silver (Atherina boyeri), Siraz (Capoeta pestai), Sudak (Sander lucioperca) species were caught in the region during the pandemic The problems experienced by the fishermen in the region; unregulated fishing, marketing, it was determined that they did not receive any government support.
Problems Experienced By Inland Water Fishermen During The Pandemic (Covid-19): The case of Yozgat Province
Keywords: Hydrobiology; Hidrobiyoloji